The evolution of the global digital platform economy: 1971–2021 - Acs, Zoltan J.; Song, Abraham K.; Szerb, László; Audretsch, David B.; Komlósi, Éva (Small business economics, 2021)
The emergence of digital technologies has significantly reduced the economic costs of data—search, storage, computation, transmission—and enabled new economic activities. Over the years, firms able to create a platform-based ecosystem have become a force of “creative construction.” Economic activities (C2C, B2C, B2B) have been reorganized around platform-based ecosystems for value creation and value appropriation, which are orchestrated by multisided platforms via the “digital hand.” To further understanding of the Digital Platform Economy, this paper provides a conceptual framework consisting of three interrelated concepts: digital technology infrastructure, multisided digital platforms, and platform-based ecosystems (users and entrepreneurs). Using a unique database over five decades, we revisit the hypothesis that new firms were needed to introduce digital technologies. Some years, like some poets and politicians, are singled out for fame far beyond the common lot and 1971 was clearly such a year. One of the events of 1971 was the inventions of the microprocessor, a computer on a chip. This invention led to the creation of the personal computer, the internet, the smart phone, and cloud computing. Over the past 50 years, economic activities have been reorganized from large bureaucratic firms to a more networked form of organization for creating value for consumers and making money for companies. To further our understanding of this digital revolution, we provide a framework consisting of three interrelated concepts: digital technology infrastructure, multisided digital platforms, and platform-based ecosystems. Using a unique database over five decades, we test the hypothesis that new firms were needed to introduce digital technologies. Countries that did not promote new firms fell behind in adopting the new technologies.